Everneath - Ashton, Brodi (New York : Balzer + Bray, 2012)
Teenaged Nikki regrets her decision to forfeit her life on Earth to become an immortal on Everneath, a world between Earth and Hell, and is given the chance to return to the Surface for six months.
Kirkus Review
Publisher's Weekly
Kirkus Review, November 2011
Publisher's Weekly, November 2011
Young Adult.
Young Adult
Keywords: Immortality -- Juvenile fiction; Supernatural -- Juvenile fiction; Immortality -- Fiction; Love -- Fiction; Supernatural -- Fiction; Immortality -- Fiction; Love stories; Supernatural -- Fiction; Love stories